Qualitative Aspects of Some Traditional Landraces of the Tomato "Piennolo" (Solanum lycopersicum L.) of the Campania Region, Southern Italy - Florinda Fratianni; Autilia Cozzolino; Antonio d'Acierno; Filomena Nazzaro; Riccardo Riccardi; Patrizia Spigno (MDPI AG, 2020)
Our study aimed to analyze some qualitative aspects of five landraces of the tomato "Piennolo," typical of the Vesuvian area, Italy, and determine the in vitro antioxidant activity. All samples showed a high °Brix value and acidity, as well as a discrete amount of reducing sugars, indicating their good quality as fresh products. They showed a high content of lycopene (up to 218 μg g−1 of fresh product) and ascorbic acid (up to 238 μg g−1 of fresh product). The content of total polyphenols was never less than 278 μg g−1 of fresh product. Hyperoside, chlorogenic and gallic acids were the most abundant polyphenols. The interrelationships between the parameters analyzed and the different landraces showed that total polyphenols could have mostly affected (ρ = 0.76) the antioxidant activity more than lycopene (ρ = −0.96). The interrelationships between the most abundant polyphenols and antioxidant activity showed that hyperoside, although the most abundant, negatively affected (ρ = −0.93) the antioxidant activity. Due to the high content of lycopene, ascorbic acid, and hyperoside, the five landraces of the tomato "Piennolo" could be considered promising in terms of their potential healthy characteristics.